Efficient Electroreduction of Nitrate into Ammonia at Ultralow Concentrations Via an Enrichment Effect. Issue 36 (7th August 2022) - Song, Zhimin; Liu, Yan; Zhong, Yongzhi; Guo, Qing; Zeng, Jie; Geng, Zhigang
Abstract: The electroreduction of nitrate (NO3 − ) pollutants to ammonia (NH3 ) offers an alternative approach for both wastewater treatment and NH3 synthesis. Numerous electrocatalysts have been reported for the electroreduction of NO3 − to NH3, but most of them demonstrate poor performance at ultralow NO3 − concentrations. In this study, a Cu‐based catalyst for electroreduction of NO3 − at ultralow concentrations is developed by encapsulating Cu nanoparticles in a porous carbon framework (Cu@C). At −0.3 V vs reversible hydrogen electrode (RHE), Cu@C achieves Faradaic efficiency for NH3 of 72.0% with 1 × 10 −3 m NO3 −, which is 3.6 times higher than that of Cu nanoparticles. Notably, at −0.9 V vs RHE, the yield rate of NH3 for Cu@C is 469.5 µg h −1 cm −2, which is the highest value reported for electrocatalysts with 1 × 10 −3 m NO3 − . An investigation of the mechanism reveals that NO3 − can be concentrated owing to the enrichment effect of the porous carbon framework in Cu@C, thereby facilitating the mass transfer of NO3 − for efficient electroreduction into NH3 at ultralow concentrations. Abstract : Cu nanoparticles encapsulated with porous carbon framework are developed as an efficient electrocatalyst for nitrate (NO3 − ) electroreduction at ultralow concentrations. Benefiting from the enrichment effect of porous carbon framework, the yield rate of NH3 for the electrocatalyst reached 469.5 µg h −1 cm −2 with 1 × 10 −3 m NO3 − .